2024
DOI: 10.1038/s41598-024-59891-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the growth promotion potential of  biochar on pea (Pisum sativum) plants under saline conditions

Shahid Fareed,
Arslan Haider,
Tahrim Ramzan
et al.

Abstract: Pea, member of the plant family Leguminosae, play a pivotal role in global food security as essential legumes. However, their production faces challenges stemming from the detrimental impacts of abiotic stressors, leading to a concerning decline in output. Salinity stress is one of the major factors that limiting the growth and productivity of pea. However, biochar amendment in soil has a potential role in alleviating the oxidative damage caused by salinity stress. The purpose of the study was to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…Globally, the saline soil is predicted to increase because of insufficient rainfall, highly-saline irrigating water, and poor agricultural management strategies, particularly in semi-arid and arid zones where evapotranspiration exceeds than precipitation [ 51 ]. In current study, it was observed that parameters related to growth, including the length of shoot and root, as well as the fresh and dry weights of shoot and root, markedly decreased under saline stress.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the saline soil is predicted to increase because of insufficient rainfall, highly-saline irrigating water, and poor agricultural management strategies, particularly in semi-arid and arid zones where evapotranspiration exceeds than precipitation [ 51 ]. In current study, it was observed that parameters related to growth, including the length of shoot and root, as well as the fresh and dry weights of shoot and root, markedly decreased under saline stress.…”
Section: Discussionmentioning
confidence: 99%